THE EFFECT OF WORK ENVIRONMENT AND WORK CULTURE ON HEALTH EMPLOYEE SATISFACTION: A STIUDY ON PUSKESMAS - Patricia Anggela, Flora; Wanta,; Komariah, Siti (International Journal of Psychosocial Rehabilitation, 2020)
This study entitled the effect of the work environment and work culture on job satisfaction of health workers in Puskesmas employees in Kota Baru District. The purpose of this study is to find out and analyze the work environment, work culture and job satisfaction, to know and analyze the effects simultaneously and partially. The research design in this study uses descriptive survey and explanatory methods. In this study the population was all employees in the Kotabaru sub-district, amounting to 104 people and used as a sample in the study. The analysis model used is multiple linear analysis. The analysis design used is to use scale techniques, scale range analysis, correlation coefficient test, coefficient of determination test, t test, and F test. The results of the research analysis obtained the average value of respondents' responses regarding the work environment by 420.125 (353 - 436 = Good), this means that the work environment at the Community Health Center in Kota Baru District was considered good. the average value of respondents' responses regarding work culture was 420,125 (353 - 436 = Good), this meant that the work culture at the Puskesmas in Kota Baru District was considered good. the average value of respondents' responses regarding job satisfaction was 417.67 (353 - 436 = Satisfied), this meant that job satisfaction at the Puskesmas in Kota Baru District was considered satisfied. Fcount value of 11.471 with a significance value of 0,000 (0,000 0.05), this means that partially the work environment has no significant effect on job satisfaction. The tcount of work culture is 3,732 with a significance level of 0,000 (0,000